A DFT study on the [VO](1+)-ZSM-5 cluster: direct methanol oxidation to formaldehyde by N2O - Fellah, Mehmet Ferdi; Onal, Isik (Royal Soc Chemistry, 2013)
The mechanism of direct oxidation of methanol to formaldehyde by N2O has been theoretically investigated by means of density functional theory over an extra framework species in ZSM-5 zeolite represented by a [(SiH3)(4)AlO4](1) [V-O](1+) cluster model. The catalytic reactivity of these species is compared with that of mononuclear (Fe-O)(1+) sites in ZSM-5 investigated in our earlier work at the same level of theory (J. Catal. 2011, 282, 191). The [V-O](1+) site in ZSM-5 zeolite shows an enhanced catalytic activity for the reaction. The calculated vibrational frequencies for grafted species on vanadium sites on the surface are in good agreement with the experimental values. According to the theoretical results obtained in this study the [V-O](1+) site in the ZSM-5 catalyst has an important role in the direct catalytic oxidation of methanol to formaldehyde by N2O.
Keywords: [No Keywords]